Beban Kerja di Laut yang Tak Terlihat: Eksplorasi Kualitatif Pengaruh Work Overload dan Stres Kerja terhadap Burnout pada Crew Kapal RORO XXX - Sandopart, Dewa Putu Yohanes Agata L. (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2023)
The aim of this study is to investigate in depth how workload that exceeds capacity limits and psychological pressure in the workplace contribute to the phenomenon of extreme fatigue among crew members serving on the RORO XXX vessel, and to identify the adaptive strategies used by officers to manage work pressure in the maritime environment. A qualitative approach with a case study design was employed. Data collection was carried out through in-depth interviews with five deck officers and participatory observation from March to April 2023, and data analysis referred to the interactive model. The exploratory results indicate that workload that is not visibly apparent has a positive correlation with increased psychological pressure, which ultimately triggers symptoms of burnout. The identified issues include quantitative and qualitative dimensions of workload exceeding individual capacity, shift work systems that disrupt biological rest rhythms, and insufficient recovery periods. The coping mechanisms applied by crew members include problem-solving efforts such as time management and team coordination, as well as emotion regulation efforts through relaxation and the use of social support. This study concludes that excessive workload and prolonged psychological pressure significantly influence the emergence of burnout, necessitating interventions in workload management along with strengthening individual capacity to cope with stress. The novelty of this research lies in its contextual exploration of burnout in the Indonesian maritime sector, which remains limited.